Implementasi Pembelajaran Pendidikan Agama Islam pada Kelas 10 Sekolah Inklusi - Enoh Nuroni Enoh Nuroni; Nurul Afrianti; Robi Mochamad Ilham (UNISBA Press, 2023)
Abstract. Islamic Islamic Religious Education (PAI) is a conscious and planned effort to prepare students to believe, understand, live, and practice the teachings of Islam through guidance, teaching, and practice activities. Education, particularly Islamic Religious Education (PAI), is provided to children who are not only physically complete but also to children who have physical or mental disorders or deficiencies. Nature High School Bandung is an educational institution that has implemented an inclusive education program because there are children with special needs (ABK) who learn together with other normal children, of course with different learning models. This school is able to accept both regular students and students with special needs, known as